Soybean fruit development and set at the node level under combined photoperiod and radiation conditions - Nico, Magalí (2016)
Fil: Nico, Magalí. Universidad de Buenos Aires. Facultad de Agronomía. Departamento de Producción Vegetal. Cátedra de Cultivos Industriales. Buenos Aires, Argentina.